Leadership style, organizational culture and job satisfaction on employee performance: Study in Food Manufacturing Companies - Sabar Sutia; Sukendar; M Saparudin; Shultonnyck Adha; Bambang Rahardjo (Privietlab, 2022)
This study builds an integrative equation model intended to provide an overall meaning about the relationship between leadership style, organizational culture, job satisfaction and its implications for employees, and how the relationship between each variable is interrelated. This research was conducted at PT. Neo Pangan Harmony by using primary and secondary data. This study took a sample of 250 people from a population of 675 people, the results of this study showed a significant relationship between each variable on employee performance.